Peaceful Families: American Muslim Efforts against Domestic Violence - Hammer, Juliane (Princeton University Press, 2019)
An in-depth look at how Muslim American organizations address domestic violence within their communitiesIn Peaceful Families, Juliane Hammer chronicles and examines the efforts, stories, arguments, and strategies of individuals and organizations doing Muslim anti–domestic violence work in the United States. Looking at connections among ethical practices, gender norms, and religious interpretation, Hammer demonstrates how Muslim advocates mobilize a rich religious tradition in community efforts against domestic violence, identifying religion and culture as resources or roadblocks to prevent harm and to restore family peace.Drawing on her interviews with Muslim advocates, service providers, and religious leaders, Hammer paints a vivid picture of the challenges such advocacy work encounters. The insecurities of American Muslim communities facing intolerance and Islamophobia lead to additional challenges in acknowledging and confronting problems of spousal abuse, and Hammer reveals how Muslim anti–domestic violence workers combine the methods of the mainstream secular anti–domestic violence movement with Muslim perspectives and interpretations. Identifying a range of Muslim anti–domestic violence approaches, Hammer argues that at certain times and situations it may be imperative to combat domestic abuse by endorsing notions of “protective patriarchy”—even though service providers may hold feminist views critical of patriarchal assumptions. Hammer links Muslim advocacy efforts to the larger domestic violence crisis in the United States, and shows how, through extensive family and community networks, advocates participate in and further debates about family, gender, and marriage in global Muslim communities.Highlighting the place of Islam as an American religion, Peaceful Families delves into the efforts made by Muslim Americans against domestic violence and the ways this refashions the society at large